A confirmatory factor analysis in a study of consumer complaint behaviour, satisfaction with complaint handling and relationship quality - A Rahman, Mohd. Khirzanbadzli; Haron, Sharifah Azizah; Paim, Laily; Osman, Syuhaily; Jaafar, Norlida (TextRoad Publication, 2016)
A study was conducted to examine the relationships of consumer complaint behaviour, satisfaction with complaint handling and relationship quality in the Malaysian mobile phone services industry. A total of 285 complainers of mobile phone users were selected as the respondents. This paper presents the results of confirmatory factor analysis (CFA), average variance extracted (AVE) and construct reliability (CR) of the study. The CFA measurement model which consist of public complaint soft action (PCSA), public complaint extreme action (PCEA), private complaint soft action (PVSA), private complaint extreme action (PVEA), satisfaction with complaint handling (SATCOM) and relationship quality show excellent goodness-of-fit with χ² = 638.781, df = 291, χ²/df = 2.195, TLI = .926, NFI = .894, CFI=.938, PNFI = .741 and RMSEA = .069 respectively. The model has shown convergent and discriminant validity with AVE and CR fulfilled the requirements. The results indicate that the model can be used for further analysis.